THD minimization for Z-source-based inverters with a novel sinusoidal PWM switching method - Ghaderı, Davood (My University, 2019)
This paper presents a modified sinusoidal pulse width modulation (SPWM) switching method for one-phase and investigated two-phase impedance-source inverter structures. The proposed structure generates pulses for a quasiZ-source converter and this block produces a unilateral voltage sine wave in the block’s output. This signal is applied to the inverter as its input wave. For this purpose, the novel SPWM method is proposed for power switches while being switched complementarily. Two power switches are used in the structure to generate the pure sinusoidal output voltage and to minimize total harmonic distortion (THD), which is an essential parameter in inverter design. The results show that the proposed method generates the pure sinusoidal voltage and current signals for resistive and inductive loads and pure voltage and improved current waves for capacitive loads in comparison with existing techniques, since the THD of the output voltage and current signals is strongly affected by the dynamic loads. This method leads to final cost improvement and reduction of the size of the system with fewer number of components, which are essential parameters for renewable energy resource applications. A mathematical model is validated with the 2017a version of MATLAB/Simulink and 1.51% and 1.33% THD values are reported for low and high power loads, respectively, in the one-phase structure and 0.95% and 0.87% in the two-phase system. Finally, a 120 W prototype has been implemented and tested. A sine-wave with 620 Vac peak to peak amplitude and 50 Hz frequency has been gained in the inverter’s output and the quality of the voltage and current waveforms has been evaluated for different two 1.8 k? and 600 ? resistive loads in the one-phase structure. Experimental results confirm all mathematical and simulation results.
Keywords: Bilgisayar Bilimleri, Yapay Zeka; Bilgisayar Bilimleri, Sibernitik; Bilgisayar Bilimleri, Donanım ve Mimari; Bilgisayar Bilimleri, Bilgi Sistemleri; Bilgisayar Bilimleri, Yazılım Mühendisliği; Bilgisayar Bilimleri, Teori ve Metotlar; Mühendislik, Elektrik ve Elektronik